2019
DOI: 10.1536/ihj.18-125
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy Using Diluted Contrast Medium for Critical Limb Ischemia in a Patient with Chronic Kidney Disease

Abstract: A high percentage of patients with critical limb ischemia have concurrent chronic kidney disease (CKD). However, endovascular therapy (EVT) can be problematic in CKD patients. Thus, we developed a method of EVT using digital subtraction angiography (DSA) with diluted contrast medium (low-concentration DSA), wherein DSA parameters were adjusted for diluted contrast angiography (1:10 dilution). Herein, we report the case of an 88-year-old woman with a foot wound and severe CKD. Her estimated glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Hayakawa et al demonstrated the efficacy of diluted contrast for lower-extremity endovascular therapy. 13 Using LC-DSA, they were able to dramatically reduce the amount of contrast required without using IVUS. Although the use of IVUS can reduce the contrast requirement in some cases, it is only useful for precise stent positioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayakawa et al demonstrated the efficacy of diluted contrast for lower-extremity endovascular therapy. 13 Using LC-DSA, they were able to dramatically reduce the amount of contrast required without using IVUS. Although the use of IVUS can reduce the contrast requirement in some cases, it is only useful for precise stent positioning.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons why PTRA has failed to show effectiveness for renal function in RCTs is the use of a large amount of contrast media (up to approximately 125 mL), 12 and PTRA may be useful for selecting patients according to lesion severity and chronic kidney disease (CKD) degree. Endovascular therapy using diluted contrast has been suggested to prevent contrast-induced nephropathy (CIN) 13 ; however, the safety and efficacy of PTRA using reduced volumes of diluted contrast are unknown.…”
Section: Introductionmentioning
confidence: 99%